2022
DOI: 10.1051/ocl/2022001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nitrogen rates on yield, yield components, and other related attributes of different rapeseed (Brassica napus L.) varieties

Abstract: Rapeseed is one of the most important oilseed crops in the world and, in Morocco, it may contribute to the improvement of food security in edible oils through developing performant cultivars and optimizing the crops management including nitrogen fertilization. The objective of this study was to evaluate the response of different Moroccan varieties to nitrogen application. Field trials were carried out at the experimental station of National School of Agriculture in Meknes, during two cropping seasons (2017–201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 41 publications
4
7
0
Order By: Relevance
“…A significant increase in N uptake was found by increasing N rates from 0 to 135 kg N ha −1 ; however, upon exceeding 135 kg N ha −1 , there was a stagnation in N concentration in biomass (Table 7). Previous studies have shown similar results, where N uptake concentration increased with N rates in canola (Chamorro et al., 2002; G. Jackson, 1999; Yahbi et al., 2022). For instance, Williams et al.…”
Section: Resultssupporting
confidence: 65%
See 3 more Smart Citations
“…A significant increase in N uptake was found by increasing N rates from 0 to 135 kg N ha −1 ; however, upon exceeding 135 kg N ha −1 , there was a stagnation in N concentration in biomass (Table 7). Previous studies have shown similar results, where N uptake concentration increased with N rates in canola (Chamorro et al., 2002; G. Jackson, 1999; Yahbi et al., 2022). For instance, Williams et al.…”
Section: Resultssupporting
confidence: 65%
“…Likewise, previous research under different climatic conditions have observed similar results, where high N rates of 150 and 200 kg N ha −1 produced greater biomass (Ma et al, 2015). Yahbi et al (2022) reported similar results because of the positive correlation of N with biomass production in canola. Karamanos et al (2004) and Malhi et al (2007) have also shown that adequate N application during the vegetative growth stages of canola can lead to increased biomass production at later stages.…”
Section: Aboveground Dry Matter Weightsupporting
confidence: 73%
See 2 more Smart Citations
“…Currently, rapeseed is gaining importance as one of the main components of the oilseeds sector in Morocco. According to the latest available data, both oilseed crops (sunflower and rapeseed) are cultivated on an area of roughly 36,000 ha, with a total production of nearly 39,000 tons [ 13 ].…”
Section: Introductionmentioning
confidence: 99%